2023
DOI: 10.3389/fimmu.2022.1044737
|View full text |Cite
|
Sign up to set email alerts
|

Drastic transformation of visceral adipose tissue and peripheral CD4 T cells in obesity

Abstract: Obesity has a pronounced effect on the immune response in systemic organs that results in not only insulin resistance but also altered immune responses to infectious diseases and malignant tumors. Obesity-associated microenvironmental changes alter transcriptional expression and metabolism in T cells, leading to alterations in T-cell differentiation, proliferation, function, and survival. Adipokines, cytokines, and lipids derived from obese visceral adipose tissue (VAT) may also contribute to the systemic T-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 146 publications
0
6
0
Order By: Relevance
“…As obesity progresses, antigens (likely self-peptides) on MHCII molecules are known to stimulate T-cell proliferation and differentiation into specific subclasses of inflammatory effectors. The persistence of VAT inflammation can be due to this factor [ 66 ]. Moreover, obese individuals have elevated levels of leptin, which can trigger the activation of T-cells and facilitate their transformation into the interferon‐gamma (IFN‐γ) -producing type 1 T helper (Th1) phenotype [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As obesity progresses, antigens (likely self-peptides) on MHCII molecules are known to stimulate T-cell proliferation and differentiation into specific subclasses of inflammatory effectors. The persistence of VAT inflammation can be due to this factor [ 66 ]. Moreover, obese individuals have elevated levels of leptin, which can trigger the activation of T-cells and facilitate their transformation into the interferon‐gamma (IFN‐γ) -producing type 1 T helper (Th1) phenotype [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…This can be a significant indicator of immunosenescence [ 64 ]. Accumulation of lipids leads to an increase in IL-6, leukemia inhibitory factor, and oncostatin M, which impede thymic functions and trigger thymocyte apoptosis [ 66 ]. When obesity decreases thymic output, peripheral T-cells undergo extensive homeostatic proliferation, which may result in T- cell senescence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The author found that in a mouse model of obesity induced by a high-fat diet, CD4 + T lymphocytes in secondary lymph nodes and visceral adipose tissue showed accelerated cellular senescence. These CD4 + T lymphocytes, which have acquired a strong inflammatory phenotype and are not suppressed by the immune checkpoint molecules programmed cell death 1 receptor and its ligand programmed cell death ligand 1, are the trigger of chronic inflammation and increased insulin resistance in visceral adipose tissue [ 69 , 70 , 71 ].…”
Section: Anti-inflammatory Effect Of Sglt2 Inhibitorsmentioning
confidence: 99%